What can we learn about commodity and credit cycles? Evidence from African commodity-exporting countries - (:unkn) unknown (My University, 2016)
This study analyzes the relationship between commodity prices and credit to the private sector in commodity-exporting developing countries, particularly three nations in Sub-Saharan Africa. In this regard, we extend the findings of non-empirical studies dealing with this issue for the case of African countries and complement the literature on the methodological side by investigating this relationship using wavelet analysis. This frequency approach is appropriate, as it takes into account investor heterogeneity and the time-variant characteristic of the studied relationship. Further, it explains the lead–lag relationship between the studied series. First, we observe that credit and commodities are strongly related over long timescales, suggesting that the credit market reacts strongly to long-term change in commodity markets and thus tends to be sensitive to persistent commodity shocks. Second, for medium and short timescales, the interaction is high and significant only during periods of turmoil. In terms of the lead–lag relationship, our results also show that the commodity market causes fluctuations in the credit market.
Keywords: African Research